Corrosion behavior of a eutectic Mg–8Li alloy in NaCl solution - Linjie Dong; Xi Liu; Jiexi Liang; Chuanqiang Li; Yong Dong; Zhengrong Zhang (Electrochemistry Communications, 2021)
The corrosion behavior of α-Mg and β-Li phases in a duplex Mg–8Li (wt. %) alloy is investigated in this work. The results reveal that the Mg–8Li alloy has a eutectic structure and is composed of equivalent α-Mg and β-Li phases. Corrosion preferentially propagates toward the α-Mg phase following initial corrosion at the α-Mg/β-Li interface. The surface of the β-Li phase is eventually destroyed after a longer immersion time. Meanwhile, the β-Li phase shows intergranular corrosion, while transgranular corrosion filaments can be seen in the α-Mg phase. Unlike the α-Mg phase, the local potential distribution on the polarization plot of the β-Li phase indicates that the surface film provides excellent protection, which is also confirmed by the results of Raman spectroscopy.